Produksi Eucheuma spp. di Sentra Akuakultur Provinsi Sulawesi Utara tahun 2023 - Usoh, Yosua; Salindeho, Indra R.N.; Mudeng, Joppy D.; Ngangi, Edwin L. A.; Kreckhoff, Reni L.; Tumembouw, Sipriana S. (Universitas Sam Ratulangi, 2024)
This study aimed to determine the seaweed production in North Sulawesi Province in 2023 and to find out the technical and non-technical factors that affect Eucheuma production in North Sulawesi. Data were collected by a survey through questionnaires, from existing records at related institutions as well as direct interviews with the farmers. The results showed that the total Eucheuma production in North Sulawesi Province in 2023 only came from the production in North Minahasa Regency, namely Nain Village as much as 473.76 tons, Nain Satu was 234.36 tons and Mantehage II Tangkasi was 131.4 tons. Thus, the total seaweed production for North Sulawesi province for 2023 was 839.52 tons. Technical and non-technical factors that influenced production were the lack quality of seaweed seeds, polluted sea waters, unpredictable weather, pests and disease attacks that have not been resolved, lack of adequate cultivation facilities and infrastructure, lack of qualified human resources (HR), limited capital and seaweed prices. Keywords: Seaweed, Nain Induk, Nain Satu, Mantehage II Tangkasi.